Citrus By-Products: Valuable Source of Bioactive Compounds for Food Applications - Andrade, Mariana A. (2022)
Citrus production produces about 15 million tons of by-products/waste worldwide every year. Due to their high content of bioactive compounds, several extraction techniques can be applied to obtain extracts rich in valuable compounds and further application into food applications. Distillation and solvent extraction continues to be the most used and applied extraction techniques, followed by newer techniques such as microwave-assisted extraction and pulsed electric field extraction. Although the composition of these extracts and essential oils directly depends on the edaphoclimatic conditions to which the fruit/plant was exposed, the main active compounds are D-limonene, carotenoids, and carbohydrates. Pectin, one of the most abundant carbohydrates present in Citrus peels, can be used as a biodegradable polymer to develop new food packaging, and the extracted bioactive compounds can be easily added directly or indirectly to foods to increase their shelf-life. One of the applications is their incorporation in active food packaging for microbiological and/or oxidation inhibition, prolonging foods’ shelf-life and, consequently, contributing to reducing food spoilage. This review highlights some of the most used and effective extraction techniques and the application of the obtained essential oils and extracts directly or indirectly (through active packaging) to foods.